2022
DOI: 10.1002/smll.202107735
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Nucleation and Growth of Inorganic Ionic Materials from Aqueous Solution: Selected Recent Developments, and Implications

Abstract: In this review article, selected, latest theoretical, and experimental developments in the field of nucleation and crystal growth of inorganic materials from aqueous solution are highlighted, with a focus on literature after 2015 and on non‐classical pathways. A key point is to emphasize the so far underappreciated role of water and solvent entropy in crystallization at all stages from solution speciation through to the final crystal. While drawing on examples from current inorganic materials where non‐classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 127 publications
1
36
0
2
Order By: Relevance
“…It has been reported that, by adding the soluble proteins extracted from the prismatic layer (calcite) or the nacreous layer (aragonite) of red abalone shell into the mineralization system, the polymorph of the precipitated CaCO 3 can switch from calcite to aragonite back and forth . The mineral morphologies can be changed via the kinetic stabilization of soluble additives to specific crystal phases. The bioinspired pathways developed to precisely control mineralization have been summarized in previous reviews. ,,, However, as the precursory phases, which have been widely found in biomineralization process, are promising in the fast and scalable fabrication of MBSMs, it is worth detailed discussions of their potentials in making MBSMs.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…It has been reported that, by adding the soluble proteins extracted from the prismatic layer (calcite) or the nacreous layer (aragonite) of red abalone shell into the mineralization system, the polymorph of the precipitated CaCO 3 can switch from calcite to aragonite back and forth . The mineral morphologies can be changed via the kinetic stabilization of soluble additives to specific crystal phases. The bioinspired pathways developed to precisely control mineralization have been summarized in previous reviews. ,,, However, as the precursory phases, which have been widely found in biomineralization process, are promising in the fast and scalable fabrication of MBSMs, it is worth detailed discussions of their potentials in making MBSMs.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Myerson et al and Vekilov [20] reviewed the evidence of the two-step nucleation mechanism where Vekilov detailed a two-step sequence scenario in which structure order is preceded by the separation of a dense, disordered liquid phase in protein systems. Gebauer and Cölfen differentiated the nature of clusters at different nucleation stages and reviewed the evidence of pre-nucleation clusters in inorganic systems [21,22]. Anwar et al [23] and Michaelides et al [24] reviewed computational approaches used to elucidate the molecular nature of nucleation and pointed to challenges in the simulation accuracy of interatomic potentials and enhanced sampling methods.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past ten years, our understanding of the mechanisms underlying the crystallisation of inorganic minerals from aqueous solutions has advanced significantly thanks to a large number of pioneering, and sometimes controversial, studies. [1][2][3][4][5] While many of the key discoveries were made for prominent mineral systems such as calcium carbonate, [6][7][8] calcium phosphate, [9][10][11] or iron (oxy)(hydr) oxides, [12][13][14] other inorganic compounds have received much less attention. In this context, one rather neglected example is magnesium hydroxide.…”
Section: Introductionmentioning
confidence: 99%